Defluorophosphorylation of fluoroalkyl peroxides for the synthesis of highly substituted furans. Issue 5 (17th February 2023) - Chu, Xue-Qiang; Cai, Song-Zhou; Chen, Jia-Wei; Yu, Zi-Lun; Ma, Mengtao; Walsh, Patrick J.; Shen, Zhi-Liang
Abstract : A highly tunable defluorophosphorylation of fluorinated peroxides for the preparation of C 3, 4-diphosphoryl furans and C 4-monophosphoryl furans under conditions with no added transition metals is disclosed. Abstract : Transformation of multifunctional materials with control over site-selectivity and chemical diversity remains challenging. Herein, we present a metal-free, one-pot strategy for the defluorophosphorylation of polyfluoroalkyl peroxides that enables expedient construction of structurally diverse phosphoryl-containing heterocyclic libraries. By judicious choice of reaction conditions, C 3, 4-diphosphoryl furans and C 4-monophosphoryl furans can be easily accessed. In addition, synthetic derivatization of the obtained organophosphorus heteroarenes to value-added monodentate and bidentate phosphines has been demonstrated. Mechanistic studies revealed that regioselective defluorophosphorylation allows divergent product formation in two reaction modes.